(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Hypertension is a chronic disease, which progresses silently and leads to many complications affecting major body organs. Hypertensive patients awareness may be developed on the various aspects regarding disease and self-care management through the health care providers. Nurses knowledge regarding hypertension plays an important role in the ability to the management of hypertension Patients [Kaur et al., 2007]. This descriptive type of cross-sectional study was conducted to assess the Nurses knowledge regarding hypertension in National Institute of Cardiovascular Diseases, (NICVD), Sher-E-Bangla Nagar, Dhaka, Bangladesh. Sample size was selected 60 nurses through purposive sampling technique. Data were collected by using the self-administer questionnaire through maintaining face to face interview of the respondents. Data analysis procedure was done by using statistical approaches. Analyzing demographic information, it has found, most of the nurses are from older age group with majority of them belong to secondary level education, significant proportion of them have done diploma in nursing. In terms of awareness, largest number of respondents has very good knowledge on concept of hypertension. They have also fairly known about management and prevention ofhypertension. However, they have limitation in knowing causes and symptom of hypertension. In addition, they have quite poor knowledge how to control hypertension. From this study, it is concluded that, hospital management require instigating different training opportunities and learning session so that nurses would have improve their knowledge.